1983
DOI: 10.1055/s-2007-969975
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of Cultivated Mulberry Tree

Abstract: From the ethyl acetate extract of the cultivated mulberry tree (Morus alba L.), two new flavonoid derivatives with a fused dihydrochalcone partial moiety were isolated, and named kuwanons K and L. The structures of kuwanons K and L were shown to be 1 and 2 respectively, on the basis of chemical and spectral data. Kuwanons K ( 1) and L ( 2) are regarded biogenetically as Diels-Alder adducts of a chalcone derivative and a dehydroprenylflavonoid derivative, and are the first example of a flavonoid derivative poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 6 publications
(12 reference statements)
1
16
0
Order By: Relevance
“…[12] The plant is reported to contain the phytoconstituent tannins, phytosterols, sitosterols, saponins, triterpenes, flavanoids, benzofuran derivatives, morusimic acid, anthocyanins, anthroquinones, glycosides and oleanolic acid as the main active principles. [1315]…”
Section: Introductionmentioning
confidence: 99%
“…[12] The plant is reported to contain the phytoconstituent tannins, phytosterols, sitosterols, saponins, triterpenes, flavanoids, benzofuran derivatives, morusimic acid, anthocyanins, anthroquinones, glycosides and oleanolic acid as the main active principles. [1315]…”
Section: Introductionmentioning
confidence: 99%
“…In the 1 H-NMR spectrum (CD 3 COCD 3 ), the proton signals of the methylcyclohexene ring were broadened, this phenomenon suggested that 1 existed as an equilibrium mixture of conformational isomers in solution, 3) and variable temperature studies were then carried out. Measured in DMSO-d 6 at 100°C, the 1 H-NMR spectrum of the methylcyclohexene ring was resolvable as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1) Previously, many novel compounds, which were regarded biogenetically as Diels-Alder adducts of dehydroprenylphenols and chalcone derivatives, were isolated from M. alba, M. lhou, M. bombycis, and so on. [2][3][4][5][6][7][8] In the course of our seeking novel bioactive compound, we started phytochemical research on the stem bark of M. macroura. The EtOH extract of M. macroura was partitioned with CHCl 3 and EtOAc, and the EtOAc fraction was sequentially subjected to column chromatography over silica gel, silica gel RP-18 and Sephadex LH-20 to give six compounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We reported the isolation and structure determination of a series of natural Diels-Alder adducts as well as of isoprenylated flavonoids isolated from the root barks of cultivated mulberry tree (1,2) and the Chinese crude drug "Sang-Bai-PI" (Japanese name "SOhakuhi") imported from the People's Republic of China (3). Some of the Diels-Alder adducts showed a significant hypotensive effect.…”
Section: Introductionmentioning
confidence: 99%